ETHICS AND DIALECTICS OR DIALECTICAL ETHICS (Andamios, Revista de Investigación Social, 2011)
The work intends (a) to reconstruct the compression that K. O. Apel has of the dialectic, (b) with special reference to the way in which she operates in environment of the ethics, and (c) to show a certain difficulty of said conception. Concretely, this situates in the fixing of the character to a priori of the conflicting elements (ideality and facticity) and at the same time in the proposal of the dissolution of the tension among them. Contrary to this, proposes toward the end a perspective that takes in consideration an insurmountable interdependency among them.
Keywords: Ethics; dialectic; ideality; facticity; a priori